2014
DOI: 10.1002/chem.201303512
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Copper(I/II)‐Catalyzed Conjugate Addition of Nitro Esters to β,γ‐Unsaturated α‐Ketoesters

Abstract: A highly enantioselective Michael addition of nitroacetates to β,γ-unsaturated α-ketoesters was developed by using chiral copper catalysts. The Michael addition products can be obtained in high yields with up to 99 % ee. With these densely functionalized products, the chiral cyclic nitrones, which are important synthetic intermediates, can be obtained in one step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…In our initial optimized study, we chose ethyl α‐nitroacetate 2a and chloro‐substituted α,β‐unsaturated pyrazolamide 1a as the model substrates. Similar with precedent finding utilizing α‐ nitroacetate as the nucleophile, the adduct 3aa was accessed as roughly 1:1 mixture of diastereomers, owing to the easy epimerization of the α‐nitroacetate stereogenic center . A systematic examination of catalyst revealed that the bifunctional squaramide afforded superior asymmetric induction than the related thiourea (Table , entry 4 vs entries 1‐3), with the quinine‐based squaramide C4 (Figure ) affording the best enantioselectivity and conversion (entry 4).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…In our initial optimized study, we chose ethyl α‐nitroacetate 2a and chloro‐substituted α,β‐unsaturated pyrazolamide 1a as the model substrates. Similar with precedent finding utilizing α‐ nitroacetate as the nucleophile, the adduct 3aa was accessed as roughly 1:1 mixture of diastereomers, owing to the easy epimerization of the α‐nitroacetate stereogenic center . A systematic examination of catalyst revealed that the bifunctional squaramide afforded superior asymmetric induction than the related thiourea (Table , entry 4 vs entries 1‐3), with the quinine‐based squaramide C4 (Figure ) affording the best enantioselectivity and conversion (entry 4).…”
Section: Resultssupporting
confidence: 60%
“…Moreover, α‐nitroacetate also provides profound derivation after the initial reaction, such as decarboxylation and denitration . However, currently this nucleophile received relatively less attention in the case of catalytic enantioselective Michael addition in comparison with other often‐used donors . Only limited electrophilic components have been investigated, including α,β‐unsaturated enones, β,γ‐unsaturated α‐ketoesters, maleimides, nitroolefins, and o ‐quinone methides …”
Section: Introductionmentioning
confidence: 99%
“…For this reason, reactions with aldehydes under Mukayama conditions failed to afford the desired products, and employment of organocatalysis afforded the aldol products in unsatisfactory yields. Nevertheless, generation of the enolate in situ with addition of TBAF was successful: Mannich reaction of 1a with Eschenmoser’s salt gave the desired elimination product 7 in 83% yield (Scheme ); α,β-unsaturated ketoesters have been efficiently employed in asymmetrical conjugate additions and cycloadditions; therefore, our method offers new substrates to assemble isoxazolines, carbazoles, dihydropyrans, or cyclic nitrones with an additional amide functional group.…”
mentioning
confidence: 99%
“…121 Copper-catalyzed Michael addition of nitro esters to β,γ-unsaturated α-ketoesters in the presence of zinc gives cyclic nitrones as a mixture of two separable diastereomers (eq 41). 122 The organocatalytic Michael addition of aldehydes to nitroolefins and in situ reductive cyclization is very convenient method for synthesis of chiral five-membered cyclic nitrones (eq 42). 123 Similarly organocatalytic addititon of β-ketosulfones to nitroolefins followed by reductive cyclization gives chiral cyclic nitrones (eq 43).…”
Section: Reaction Of Oximesmentioning
confidence: 99%